INDONESIAN'S EFFORTS TO INCREASE COFFEE EXPORTS TO JAPAN IN THE PERIOD 2013-2017 - Athilla Muhammad Luthfi; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This work is an analysis of international political economy studies. This study discusses Indonesia's efforts to increase coffee exports to Japan in the period 2013-2017. The export of Indonesian coffee to Japan is the biggest opportunity for Indonesia in the Asian region. The problem with Indonesian coffee lies in the unstable quality of coffee, this is because 95% of Indonesian coffee plantations are held by the people so that it is difficult to equalize the standard of good quality coffee.            This research uses a liberalism perspective, and is supported by the theory of international trade. This research uses qualitative methods with descriptive analysis. The data collection technique in this research is to conduct library research. Namely analyzing data relating to the problem, with data collection techniques from literature in the form of  books, magazines, newspapers and visits to internet sites and other sources that support research.            This research shows that the efforts that have been made by Indonesia can be divided into two, namely  internal and external efforts. Internal efforts refer to improving the quality, productivity and production of Indonesian coffee with the issuance of the Minister of Agriculture Regulation No. 88 year 2017, the making of ISCoffee, and the 2013-2017 National Coffee Development Activities. External efforts that have been made include efforts to increase coffee exports to Japan through the IJEPA, remove non-tariff barriers to coffee exports to Japan in the case of carbaryl, and promotion of Indonesian coffee exports to Japan. Keywords:International Trade,  Export, Coffee, IJEPA